Games, norms, rule taxonomies, and existence: A review from systemic materialism - Ordóñez-González, José Rafael (DICERE Revista de Derecho y Estudios Internacionales, 2024)
This article provides a review from the perspective of systemic materialism of some taxonomies of rules applicable to diverse community normative contexts such as games, sports, law, religion, and criminal organizations. It examines the connections between the taxonomies of norms, highlighting the presence of accepted rules that define actions permitted, prohibited, or obligatory in both contexts. The normative classifications proposed by philosophers such as Rawls, Searle, and Bulygin are analyzed, recognizing the need to update them in line with systemic materialism. A new taxonomy of rules is proposed based on a 4-tuple that includes linguistic expression, designated construct, associated social function, and development time of the function. This perspective allows for distinguishing between different types of rules according to their function at the social material level, promoting a deeper understanding of legal and social reality.